Faktor-Faktor yang Memengaruhi Niat Menggunakan Teknologi AI untuk Evaluasi Usaha pada Pelaku UMKM di DKI Jakarta: Perspektif Task-Technology Fit - Kikana Yusuf; Osly Usman; Stanny Dewanty Rehatta (Indo Publishing, 2026)
AI utilization within business environments has undergone increasingly conspicuous acceleration, encompassing MSME operators conducting business evaluation activities within its expanding reach. Notwithstanding, the adoption process has not transpired without impediment, with diverse considerations persisting, encompassing task-technology alignment, AI capability configurations, individual user readiness, and surrounding social environmental conditions. This investigational endeavor is directed toward scrutinizing AI usage tendencies within business evaluation activities through the TTF perspectival lens. All information was harvested through quantitative survey operationalization involving DKI Jakarta-domiciled MSME operators who have utilized or bear interest toward AI technology, subsequently processed through SEM-PLS approach. Final outputs reveal that task characteristics, technology characteristics, and individual characteristics deliver meaningful contributions toward task-technology fit formation, whilst social characteristics fail to demonstrate adequate contributory presence. Task-technology fit is likewise confirmed as a propelling element toward AI usage intention emergence. Said condition signals that task-need and technology-capability alignment, accompanied by individual user readiness, commands more dominant influence compared to social environmental propulsion. Consequently, AI adoption decisions within the MSME sector bear greater determination by functional aspects and personal readiness than by social pressure or support configurations.